154 PROBIOTICS: OBSERVATION IN PRACTICAL MEDICINE. (15th December 2022) - Acquistapace, Flavio; Camponovo, Claudio; Odello, Tania; Negrini, Alice; Graziano, Elisa
Abstract: Background: There are several, even recent, basic research studies that have demonstrated the microbiota's cause for the predisposition and development of degenerative disorders and risk factors: cardiovascular diseases, obesity, metabolic syndrome and diabetes. Studies, knowledge and communication on probiotics have gone and are increasingly growing, so much so that almost a "trend" of the probiotic has developed. The importance of defining the "probiotic", developing knowledge and clinical research, or evaluating the results in real clinical practice, is essential for the appropriate use for the benefit of the person. The doctor has and must have a central and primary role. Purpose: The study, which we conducted in clinical practice, is of an observational type, and has as its primary outcome that of evaluating the impact of nutriceutic integration with probiotics on risk factors of inflammatory and metabolic markers and as a secondary outcome the functional capacity and perception of psychophysical health. Methods: Out of 70 patients followed, 50 patients were selected and evaluated for homogeneity and adherence characteristics. Eligibility characteristics below: risk profile, familiarity for cardiovascular diseases, dysendocrine disorders, overweight and obesity, hypertension, diabetes, hypercholesterolemia, hypertriglyceridemia, fatigue syndrome, neurovegetative dystonia. The evaluation of probiotic therapy was carried out in two stages on the basis of the following parameters: psychophysical perception of the state of health, using the SF-36 Questionnaire, functional capacity by means of the physical ability test (Six Minute Walking Test 6MWT or Walking Test), blood tests: PCR, Vitamins, lipid profile. The nutraceutical scheme consists of taking 2cps after breakfast and 2 cps after Enterelle's dinner, during the first week. Bifiselle, second week, Ramnoselle third week Serobrain 1 cps after breakfast fourth week. Serobioma, one tablet per day, for 3 months: maintenance phase. Results and Conclusions: The observational study in real practice indicated an efficacy of the probiotic nutraceutical treatment on patients with regard to the reduction of the measurable risk profile, improvement of the perception of health including objective level of functional capacity, stabilization of the levels of vitamins (vit B and D).